COMPARISON STUDY OF TOP DEVELOPMENT BOARDS IN THE CONTEXT OF IOT (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2022)
The Internet of Things (IoT) is an uprising technology. However, this was possible due to an open-source hardware project - Arduino Uno, which made IoT accessible to the people. Combined, the IoT provided the means and methodologies, while the Arduino offered an easy-to-use, easy-to-program system which led to an ascending trend for both. After more than ten years of successful collaboration between IoT and Arduino systems, several new competitors launched development boards created especially for IoT. The most popular are Raspberry Pi Pico, ESP8266, STM32, etc. This paper applied a multicriterial analysis (MCA) to rank the performances of the development mentioned above boards in the IoT context. The main goal is to establish if Arduino Uno, which dominated the market, will continue to lead, or will be replaced by one of its competitors.
Keywords: Arduino Uno; Raspberry Pi; Wi-Fi microchip ESP8266; Internet of things (IoT); Multicriterial analysis